2020
DOI: 10.3390/agronomy10060815
|View full text |Cite
|
Sign up to set email alerts
|

Arbuscular Mycorrhizal Fungi as Potential Agents in Ameliorating Heavy Metal Stress in Plants

Abstract: Heavy metal accumulation in plants is a severe environmental problem, rising at an expeditious rate. Heavy metals such as cadmium, arsenic, mercury and lead are known environmental pollutants that exert noxious effects on the morpho-physiological and biological attributes of a plant. Due to their mobile nature, they have become an extended part of the food chain and affect human health. Arbuscular mycorrhizal fungi ameliorate metal toxicity as they intensify the plant’s ability to tolerate metal stress. Mycorr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
50
0
3

Year Published

2020
2020
2023
2023

Publication Types

Select...
3
3
2

Relationship

1
7

Authors

Journals

citations
Cited by 130 publications
(54 citation statements)
references
References 177 publications
(169 reference statements)
1
50
0
3
Order By: Relevance
“…These results are in agreement with other works [ 15 , 48 , 49 , 50 ] demonstrating that phytoremediation can be increased by inoculating P. vittata with selected AMF. In fact, AMF play a key role in the mobilization/immobilization of metal ions and could alter their availability to plants [ 21 ]. AMF may lead to protective effects through changes in metals solubility mediated by changes in the soil solution pH, or by immobilizing heavy metals in and on fungal biomass [ 51 ] Moreover, ferns inoculated with the AMF Funneliformis mosseae exhibited higher activities of antioxidant enzymes [ 49 ] and up-regulation of multiple forms of glyceraldehyde-3-36 phosphate dehydrogenase, and other enzymes playing a central role of glycolytic enzymes in arsenic metabolism [ 18 ].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…These results are in agreement with other works [ 15 , 48 , 49 , 50 ] demonstrating that phytoremediation can be increased by inoculating P. vittata with selected AMF. In fact, AMF play a key role in the mobilization/immobilization of metal ions and could alter their availability to plants [ 21 ]. AMF may lead to protective effects through changes in metals solubility mediated by changes in the soil solution pH, or by immobilizing heavy metals in and on fungal biomass [ 51 ] Moreover, ferns inoculated with the AMF Funneliformis mosseae exhibited higher activities of antioxidant enzymes [ 49 ] and up-regulation of multiple forms of glyceraldehyde-3-36 phosphate dehydrogenase, and other enzymes playing a central role of glycolytic enzymes in arsenic metabolism [ 18 ].…”
Section: Discussionmentioning
confidence: 99%
“…Arbuscular mycorrhizal fungi (AMF) are symbiotic microscopic fungi belonging to the Glomeromycotina, subphylum of phylum Mucoromycota [ 20 ], able to positively influence plant performance in many ways, including by enhancement of heavy metal/metalloid stress tolerance [ 21 ]. AMF colonize the roots of most terrestrial plants [ 22 ], including ferns; once the symbiosis is established, they improve plant nutrition [ 23 ], modify root architecture [ 24 ], and promote plant tolerance or resistance to pathogens [ 25 , 26 , 27 ], drought [ 28 ], and salinity [ 29 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Overproduction of ROS in the human body damages diverse biomolecules via redox reactions and leads to cellular damage, mutation, cell death, and aging [ 40 , 41 , 42 , 43 ]. ROS are also implicated in several chronic illnesses and other age-related disorders.…”
Section: Free Radicals and Agingmentioning
confidence: 99%
“…Aluminum was determined in the formation of High-Grade Al Deposits of the Dopolan Karst Type Bauxite, Iran [38] while pollutant of arsenic, lead, and copper were also detected in bauxite mining soil from Bintan Island, Indonesia [39]. AM fungi ameliorate metal toxicity as they intensify the plant's ability to tolerate metal stress [40]. Agus et al [41] reported that fast-growing legume species of Pongamia pinnata and AM fungi application can not only increase nutrient contents of post-coal mining soil but also increases iron absorption, which is mostly accumulated in the root system.…”
Section: Growth Of Colonized Forest Tree Seedlings In the Nurserymentioning
confidence: 99%